PERDAGANGAN MANUSIA DI PINTU GERBANG NUSANTARA: TANGGUNG JAWAB GEREJA SEBAGAI KOMUNITAS PEMBEBAS - Pasaribu, George Rudi Hartono; Purba, Gomgom; Harefa, Otieli (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2025)
This article explores the reality of human trafficking in the Batam and Riau Islands region, one of Indonesia’s primary trafficking hotspots due to its strategic location as a gateway to neighboring countries. Using a qualitative case study approach, this research investigates the awareness and role of local churches in responding to this phenomenon. The findings reveal that many churches remain unaware of the theological connection between faith and social responsibility toward trafficking victims. However, some churches have begun transforming into liberating communities through ministries of restoration and advocacy. This study recommends a transformative diakonia approach and liberation theology as frameworks for the church to act as an agent of social justice in a world marked by oppression.